Covid-19 Infection in Elderly with Comorbids - Edo Yudistira; Roza Mulyana (Biomedical Journal of Indonesia, 2021)
The senior population has a higher risk of contracting Covid-19 and is at risk of developing more severe disease. This is due to physiological changes in old age, which causes a decrease in immune function accompanied by an increase in comorbid disorders such as diabetes, hypertension, heart disease, lung disease, and dementia. WHO reports that the mortality rate for Covid-19 patients in the elderly above 80 years in China is around 21.9%, Italy is about 89% at the age above 70 years, and the United States is 85% at the age of 65 years and over. Delirium syndrome often appears as the primary complaint or infrequently; it occurs on the first day the patient is treated and shows fluctuating symptoms. Symptoms of delirium, such as disorientation, difficulty concentrating, and inattention, often occur in the elderly and are associated with a poor prognosis. Management of geriatric patients with covid 19 must be carried out thoroughly and completely, especially in geriatric patients with comorbidities. Management includes primary diseases, namely Covid-19 infection, delirium, nutritional therapy, blood sugar, family education for patient assistance, maintaining the patient's body and environment cleanliness, oral hygiene, and, last but not least, moral support from the family for the patient. With complete management, elderly patients with various comorbid can survive the Covid-19 infection.